Commercial sanitary napkins vs. Reusable cloth pads : analyzing the influence of plastics on domestic solid waste and user{u2019}s behaviour changes - Daewi Hla Myint; Visvanathan, C.; Chatterjee, Joyee S.; Xue, Wenchao; Government of Japan (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
Management menstrual hygiene management is still lacking in Myanmar, and lack of availability to hygiene products is a major concern. The aim of this study is to investigate the current situation of feminine hygiene products in Myanmar and Thailand in terms of social, technological, policy, and market analysis. Laboratory experiments were conducted to estimate waste generation and the composition of plastic in sanitary napkins and reusable cloth pads. According to the findings of the survey, sanitary napkin users would not like to change their behavior since they are habituated to using sanitary napkins as well as have more hygienic concerns, furthermore alternative products are difficult to obtain and rarely found on the market. Alternative product opportunities included the prospect of eco friendly products, as environmental concerns have grown in recent years however, the market limitation was the weakness of these items. Government engagement and partnership with NGOs, on the other hand, are critical to raising hygiene product awareness and accelerating the use of alternative products. Government regulations for hygiene waste management, promotion of hygiene products market and public awareness are various aspects of menstrual hygiene management in Myanmar to address.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Marine Plastics Abatement
Research studies project report (M.) - Asian Institute of Technology, 2021
Keywords: Plastics -- Environmental aspects -- Myanmar; Sanitary napkins -- Myanmar; Waste management